Creating a Role - Stanislavski, Constantin; Hapgood, Elizabeth Reynolds; Popper, Hermine I. (London Bloomsbury, 2014)
Creating A Role is the third book - alongside the international bestseller An Actor Prepares and Building A Character - in the series of influential translations that introduced Stanislavski's acting 'system' to the English-speaking world. Here Stanislavski describes the elaborate preparation that an actor must undergo before the actual performance itself. Now published in the Bloomsbury Revelations series to mark the 150th anniversary of Stanislavski's birth, the book includes the director's analysis of such works as Othello and Gogol's Inspector General.
Keywords: Acting